Pedagogical Skills of Teacher - Tajibaeva Mahmuda Rustamovna; Ikromova Kamola Askarovna (Genius Journals, 2021)
The purpose of this work is to consider the subjective characteristics of the teacher's personality, and then we will touch on only the first three groups of the structure of subjective properties. The place and functions of the teacher in society, the requirements of society and social expectations in relation to the personality and activities of the teacher are also considered.
Keywords: Subjective Characteristics; Requirements Of Society; Activities Of The Teacher; Social Expectations